Simulation of alkali gaseous condensation and fly ash viscous capture-induced dual slagging on mid-temperature heating surface of biomass boiler - Tongyu QIU; Haining SU; Yuting SUN; Yiming ZHU; Xuebin WANG; Tianhua YANG (Meitan xuebao, 2024)
As a renewable energy source with zero CO2 emission, biomass has a good application potential in partially replacing fossil fuels for power generation. However, biomass fuels generally contain high content of alkali metal components that easily precipitate and condense to form a viscous initial deposition layer on the heating surface during combustion. Capture of fly ash by viscous surface is thus enhanced, resulting in further severe slagging in the biomass-fired boiler. Aiming at these problems, the adhesion characteristics of the initial deposition layer in the mid-temperature superheater of biomass boiler has been calculated using FactSage software. Combined with the critical velocity model, an integrated model of slagging considering KCl condensation and fly ash viscous capture is established. The user-defined function (UDF) is employed with ANSYS FLUENT software to simulate the fouling behavior of the heating surface of the mid-temperature superheater of biomass boiler, and field sampling results are used for model validation. The results show that the deposition rate in the mid-temperature superheater is consistent with the sampling results. The increase of wall temperature has little effect on the ash impaction efficiency, but the inhibition of KCl condensation leads to fewer deposition. The change of flue gas inlet velocity affects the condensation and impaction efficiency. The impaction efficiency of large particles (50, 80 μm) increases with the increase of flue gas velocity, while the small particles of 10 μm are more easily captured by the viscous wall, resulting in higher deposition efficiency. Under a same gas inlet velocity, the fly ash particles with diameter of 50 μm and 80 μm dominate the deposition. Overall, the contribution to slagging of mid-temperature superheater by alkali gaseous condensation is significant. The mass of KCl direct condensation accounts for 5.41% of the total deposition mass, while the mass of fly ash viscous capture accounts for 19.24%. The proposed model is suitable for predicting ash deposition and fouling on mid-temperature heating surface (about 700 ℃) represented by a mid-temperature superheater of a biomass boiler.